2022
DOI: 10.1093/nop/npac007
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of radiotherapy following brain metastases surgery

Abstract: Background There is growing evidence supporting the need for a short time delay before starting radiotherapy (RT) treatment post-surgery for most optimal responses. The timing of RT initiation and effects on outcomes have been evaluated in a variety of malignancies, but the relationship remains to be well established for brain metastasis. Methods Retrospective study of 176 patients (aged 18 to 89 years) with brain metastases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…It is also important to note that receipt of adjuvant radiation early can improve patient burden by reducing visits, scan requirements, and time to resumption of systemic cancer-directed therapy. 14,15,20 Importantly, OS was not different between RapidRT and StanRT cohorts or between cohorts stratified by time to radiation at any time point. This suggests that other retrospective studies that demonstrated poor survival in patients receiving ultra-early irradiation (<22-23 days) 14,15 may have been confounded by other potential correlates, such as rapidly progressive extracranial extent of disease.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…It is also important to note that receipt of adjuvant radiation early can improve patient burden by reducing visits, scan requirements, and time to resumption of systemic cancer-directed therapy. 14,15,20 Importantly, OS was not different between RapidRT and StanRT cohorts or between cohorts stratified by time to radiation at any time point. This suggests that other retrospective studies that demonstrated poor survival in patients receiving ultra-early irradiation (<22-23 days) 14,15 may have been confounded by other potential correlates, such as rapidly progressive extracranial extent of disease.…”
Section: Discussionmentioning
confidence: 88%
“…Once the analyses were stratified by time to radiation within the larger combined cohort, this association became clearer. It is also important to note that receipt of adjuvant radiation early can improve patient burden by reducing visits, scan requirements, and time to resumption of systemic cancer-directed therapy . Importantly, OS was not different between RapidRT and StanRT cohorts or between cohorts stratified by time to radiation at any time point.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations